2012
DOI: 10.1029/2012gl054406
|View full text |Cite
|
Sign up to set email alerts
|

Soil‐derived sulfate in atmospheric dust particles at Taklimakan desert

Abstract: Dust‐associated sulfate is believed to be a key species which can alter the physical and chemical properties of dust particles in the atmosphere. Its occurrence in the particles has usually been considered to be the consequence of particles' aging in the air although it is present in some crustal minerals. Our observation at the north and south edge of Taklimakan desert, one of the largest dust sources in the Northern Hemisphere, during a dust episode in April 2008 revealed that sulfate in atmospheric dust sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 47 publications
4
28
0
Order By: Relevance
“…As shown in Fig. 4a, extremely high levels of sulfate were observed during the dust storm period (Phase I), with a peak of 180 µg m −3 in the first hour, accounting for 2.3 % of the TSP mass (Table 1), which falls in the range reported for the airborne dust in the Taklamakan desert by Wu et al (2012). Due to the second peak of the dust storm that arrived in Xi'an at noon on 10 March, SO 2− 4 concentration showed a moderate peak as did TSP (see the inserted figure in Fig.…”
Section: Hourly Changes In Chemical Compositions Of Ambient Particlesmentioning
confidence: 67%
See 1 more Smart Citation
“…As shown in Fig. 4a, extremely high levels of sulfate were observed during the dust storm period (Phase I), with a peak of 180 µg m −3 in the first hour, accounting for 2.3 % of the TSP mass (Table 1), which falls in the range reported for the airborne dust in the Taklamakan desert by Wu et al (2012). Due to the second peak of the dust storm that arrived in Xi'an at noon on 10 March, SO 2− 4 concentration showed a moderate peak as did TSP (see the inserted figure in Fig.…”
Section: Hourly Changes In Chemical Compositions Of Ambient Particlesmentioning
confidence: 67%
“…Our previous investigation on the impact of Asian dust storms on Xi'an aerosols in the spring of 2009 found that 88 % (in mass) of airborne particulate sulfate originated from Gobi desert soil in the presence of the dust storm . A recent study on the atmospheric aerosols collected in the Taklamakan desert also reported that airborne particles in the desert are abundant in sulfate, which accounts for about 4 % of the particle mass with no significant difference for particles with different sizes (Wu et al, 2012). WSOC / WSON ratios are higher in the dust storm and transition periods and lower in the non-dust period, which can be ascribed to more WSON species emitted from anthropogenic sources such as agricultural fertilizer and livestock dejecta (Cape et al, 2011;Chen et al, 2010;Wang et al, 2010).…”
Section: Hourly Changes In Chemical Compositions Of Ambient Particlesmentioning
confidence: 99%
“…The observed average concentration of fSO 4 2-was 8.9 µg m -3 in episode D, while NAQPMS and CMAQ simulations of anthropogenic fSO 4 2-indicated 3.2 µg m -3 and 2.9 µg m -3 , respectively. After considering soil-derived fSO 4 2-(4% of fine mode dust (Wu et al, 2012)) and heterogeneous reactions on dust particles, NAQPMS simulated a total fSO 4 2-concentration of 4.8 µg m -3 , 42.7% lower than the observation. This indicates that current models may miss certain emissions of SO 2 or chemical mechanisms that promote the conversion of SO 2 to SO 4 2-when dust is present.…”
Section: Characteristics Of the Three Air Pollution Episodes In Fukuokamentioning
confidence: 99%
“…This result means that the sulfate in the dust samples at Xi'an was very likely one of the original components of the dust particles, i.e., the socalled soil-derived sulfate in desert dust. It has been found that dust at desert areas contains substantial soil-derived sulfate (Abuduwaili et al, 2008;Sun et al, 2010;Wu et al, 2012;Yabuki et al, 2005;Zhang et al, 2009), and sulfate was confirmed in long-distancetransported dust in downstream areas in a small number of studies Wu et al, 2012). For these reasons, we consider the sulfate detected in the dust samples right after the cold front to be mainly from the desert areas as soil-derived sulfate rather than sulfate produced by chemical conversions on the particle surface when the particles floated in the air.…”
Section: Sulfatementioning
confidence: 94%
“…A study at the Taklimakan Desert pointed out that in some cases the content of sulfate in dust particles might not change even when the particles traveled over a long distance. The dust particles contained substantial sulfate (∼ 4 % by mass), which was from the surface soil (Wu et al, 2012). It was also found that, for a dust plume lofted from the surface by a synoptic mid-latitude cyclone, the plume did not mix significantly with adjacent air parcels polluted by anthropogenic sources; the dust plume and the polluted air were separated as two air parcels by the cold front associated with the cyclone (Bates et al, 2004;Tsai et al, 2014;Wang et al, 2013;Zhang et al, 2005).…”
Section: Introductionmentioning
confidence: 96%